Pelatihan Wondershare Filmora 9 Untuk Peningkatan Promosi UMKM profile Lab.Scarpe di Bandar Khalipah, Kec. Percut Sei Tuan, Kabupaten Deli Serdang, Sumatera Utara - Haida Dafitri; Nur Wulan; Rachmat Aulia; Ilham Faisal; Adelia Atmaja (LPPM STIKOM Tunas Bangsa, 2022)
One of the determinants of the success of UMKM is the importance of promotion. Promotion can be done conventionally by making brochures, flyers or banners but can also be done digitally through mass media. Making a promotional video for UMKM profiles is one of the ways to promote to the public by utilizing digital promotions in the form of videos. In the new normal era, promotions in the digital field are in great demand, and services without leaving the house are an alternative that will be chosen by the public. This research is intended to introduce an UMKM in order to promote these UMKM digitally to help increase sales in order to improve the economy after the Covid-19 pandemic. Making an interesting UMKM Video Profile is one of them by using the Wondershare Filmora 9 video editor application, but unfortunately the owner and workers in the field of UMKM do not know the use and utilization of these applications. For this reason, the writer and the team were asked to provide training in making UMKM profiles with the Wondershare Filmora application. It is hoped that this training can help UMKM owners and workers provide ideas in making interesting and interactive UMKM video profiles so that later they can increase revenue and sales of UMKM Lab Scarpe Products in Bandar Khalipah, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. The training was carried out such as providing information and the use of Wondershare Filmora 9, in making UMKM video profiles.